Chlorine-containing COFs solid electrolyte and preparation method and application thereof

By using chlorine-containing COFs as solid electrolytes in lithium-ion batteries, the lithium dendrites problem is solved, and the ionic conductivity, electrochemical stability and charge and discharge performance of the battery are improved.

CN119842034AInactive Publication Date: 2025-04-18INNER MONGOLIA UNIV OF TECH

Patent Information

Application Number
CN202510327406.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-19
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the lithium dendrites problem in lithium-ion batteries, resulting in poor interface stability and charge and discharge performance.

Method used

Chlorine-containing COFs (carbon-based skeleton organic frame material) are used as solid electrolytes, and the ionic conductivity and electrochemical stability of the electrolyte are improved by introducing chlorine elements. The specific method includes the use of raw materials such as 2,4,6-triformyl phthalglucoside and chlorine-containing 1,4-diaminobenzene or 2,5-dichloro-1,4-phenylenediamine to synthesize chlorine-containing COFs materials such as TpCl-1 and TpCl-2 by solvothermal method.

Benefits of technology

The ion conductivity, lithium ion migration number and electrochemical window of lithium ion batteries are significantly improved, the interface stability and charging and discharge performance of the battery are enhanced, the growth of lithium dendrites is reduced, and the energy density and cycling stability of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119842034A_ABST
    Figure CN119842034A_ABST
Patent Text Reader

Abstract

The invention discloses a chlorine-containing COFs solid electrolyte and a preparation method and application thereof, and relates to the technical field of batteries, the chlorine-containing COFs solid electrolyte comprises two types, specifically TpCl-1 and TpCl-2; a preparation method of the TpCl-1 comprises the following steps: weighing Tp and PaCl-1 / PaCl-2, putting the weighed Tp and PaCl-1 / PaCl-2 into a mixed solvent of mesitylene and 1, 4-dioxane, dropwise adding glacial acetic acid, and carrying out ultrasonic treatment until the Tp and the PaCl-1 / PaCl-2 are uniformly dispersed; under the nitrogen atmosphere, putting the mixed solution into a liquid nitrogen bath in a sealed manner, repeatedly freezing and unfreezing for three times, and reacting at 120 DEG C for 72 hours after the room temperature is recovered; after the reaction is finished, washing an obtained solid material with acetone, methanol and tetrahydrofuran for 3-5 times respectively until a washing solution is colorless; and finally, drying at the temperature of 90 DEG C under reduced pressure for 12 hours to remove the solvent to obtain dark red powder, namely TpCl-1 / TpCl-2. The electrochemical performance of the chlorine-containing COFs solid electrolyte (TpCl-1 and TpCl-2) disclosed by the invention is obviously enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a chlorine-containing COFs solid electrolyte and a preparation method and application thereof. Background Art

[0002] Halide solid electrolytes have good ionic conductivity, a wide electrochemical stability window, and good compatibility with high-voltage oxide cathodes, and are candidate materials for high-performance all-solid-state battery electrolytes. The electrochemical performance can be improved by introducing materials containing halogen elements into the matrix. For example, the addition of Li3YBr2Cl4 can improve the overall mechanical and electrochemical properties of the electrolyte material. In order to solve the problem of lithium dendrites, researchers have proposed a fluorine-containing solid electrolyte. The trifluoro group can enhance the stability of the framework channel and form a stable interfacial phase at the interface between the electrolyte and metallic lithium, which not only improves the reversibility of the lithium anode and the interfacial charge transfer efficiency, but also ensures uniform and dense lithium deposition. Halogen-containing groups facilitate lithium ion transport and provide hopping sites for rapid transport, thereby achieving high ionic conductivity and low activation energy. The high oxidation limit of chloride-based solid electrolytes (~4.3V vs. Li + / Li) is considered to have a high compatibility and applicability with the positive electrode material. In summary, it is feasible to select chlorine with high economic benefits to prepare COFs materials in lithium-ion batteries. Summary of the invention

[0003] In view of the above problems, the present invention provides a chlorine-containing COFs solid electrolyte and a preparation method and application thereof.

[0004] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing a chlorine-containing COFs solid electrolyte. The chlorine-containing COFs solid electrolyte includes two types, specifically: TpCl-1 and TpCl-2; The preparation method of TpCl-1 is as follows: 2,4,6-triformylphloroglucinol (Tp) and 2-chloro-1,4-diaminobenzene (PaCl-1) are weighed and placed in a mixed solvent of mesitylene and 1,4-dioxane, glacial acetic acid is added dropwise, and ultrasonication is performed until uniform dispersion to obtain a mixed solution; under a nitrogen atmosphere, the mixed solution is sealed and placed in a liquid nitrogen bath, and repeatedly frozen and thawed three times, and after returning to room temperature, the mixed solution is reacted at 120° C. for 72 hours; after the reaction is completed, the obtained solid material is washed with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing solution is colorless; finally, the solvent is removed by drying under reduced pressure at 90° C. for 12 hours to obtain a dark red powder, namely TpCl-1; The preparation method of TpCl-2 is as follows: weigh 2,4,6-triformylphloroglucinol (Tp) and 2,5-dichloro-1,4-phenylenediamine (PaCl-2), place them in a mixed solvent of mesitylene and 1,4-dioxane, drop glacial acetic acid, and perform ultrasonication until uniform dispersion to obtain a mixed solution; under a nitrogen atmosphere, seal the mixed solution in a liquid nitrogen bath, freeze-thaw repeatedly three times, and react at 120° C. for 72 hours after returning to room temperature; after the reaction is completed, wash the obtained solid material with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing solution is colorless; finally, dry under reduced pressure at 90° C. for 12 hours to remove the solvent to obtain a dark red powder, namely TpCl-2.

[0005] Furthermore, in the preparation of TpCl-1, the mass of 2,4,6-triformylphloroglucinol is 210 mg, and the mass of 2-chloro-1,4-diaminobenzene is 214 mg.

[0006] Furthermore, in the preparation of TpCl-1, the volume of the mixed solvent is 30 mL; in the mixed solvent, the volume ratio of mesitylene to 1,4-dioxane is 1:1; the concentration of glacial acetic acid is 6 mol·L -1 , the volume is 4mL.

[0007] Furthermore, in the preparation of TpCl-2, the mass of 2,4,6-triformylphloroglucinol is 210 mg, and the mass of 2,5-dichloro-1,4-phenylenediamine is 265 mg.

[0008] Furthermore, in the preparation of TpCl-2, the volume of the mixed solvent is 30 mL; in the mixed solvent, the volume ratio of mesitylene to 1,4-dioxane is 1:1; the concentration of glacial acetic acid is 6 mol·L -1 , the volume is 4mL.

[0009] The present invention also provides a chlorine-containing COFs solid electrolyte prepared by the preparation method of the chlorine-containing COFs solid electrolyte.

[0010] The present invention also provides an application of the chlorine-containing COFs solid electrolyte in the preparation of a lithium metal battery.

[0011] When the electrolyte of the present invention is used, the electrolyte needs to be prepared into an electrolyte membrane after slurry preparation. The slurry preparation method is: the COFs material obtained above and lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) are fully mixed and stirred in an NMP (N-methylpyrrolidone) solution for 12 hours to allow the lithium salt to fully enter the pores of the COFs, and a binder polyvinylidene fluoride (PVDF) (COFs: LiTFSI: PVDF = 1:0.7:0.7 by mass ratio) is added and stirred for 12 hours to form a slurry, which is transferred to a mold, placed at 90°C and dried under reduced pressure for 12 hours to remove the solvent, to obtain a solid electrolyte membrane, and cut to size for standby use.

[0012] Compared with the prior art, the present invention has the following beneficial effects: In the present invention, the chlorine-containing COFs solid electrolyte (TpCl-1 and TpCl-2) showed significant improvements in many aspects. The room temperature ionic conductivity of TpPa was 6.37×10 -4 S cm -1 , while the room temperature ionic conductivity of TpCl-1 and TpCl-2 increased to 3.02×10 -3 S cm -1 and 3.23×10 -3 S cm -1 , that is, the introduction of chlorine significantly improves the ionic conductivity of the electrolyte, thanks to the strong electron-withdrawing property of chlorine, which can fix the free anions in the electrolyte, thereby accelerating the transmission of lithium ions. The lithium ion migration number of TpPa is 0.75, while the lithium ion migration numbers of TpCl-1 and TpCl-2 are increased to 0.81 and 0.85, respectively. The higher lithium ion migration number indicates that the transmission efficiency of lithium ions in the electrolyte is higher, which helps to improve the charge and discharge performance of the battery. The electrochemical window of TpPa is 1.0-4.0V, while the electrochemical windows of TpCl-1 and TpCl-2 are widened to 1.0-4.5V and 1.0-5.0V, respectively. That is, the introduction of chlorine enhances the electrochemical stability of the electrolyte, enabling it to adapt to higher voltage positive electrode materials, and improving the energy density and cycle stability of the battery. In the stripping and plating test of symmetrical lithium batteries, the polarization voltages of TpCl-1 and TpCl-2 at different current densities were lower than that of TpPa, indicating that the introduction of chlorine can effectively inhibit the growth of lithium dendrites and improve the interfacial stability and safety of the battery. The cycling performance of TpCl-1 and TpCl-2 at 1C and 0.2C current densities were better than that of TpPa, with discharge capacity retention rates of 71% and 75%, respectively. In addition, after high-rate cycling, TpCl-1 and TpCl-2 can still recover a high specific capacity, indicating that they have excellent reversibility and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1The XRD spectra of (a) TpPa, (b) TpCl-1, and (c) TpCl-2 of the present invention; (d) comparison of powder diffraction errors (the refined experimental data is red, the simulated data is blue, and the difference between the experimental value and the simulated refinement is black); Figure 2 FT-IR spectra of (a) TpPa, (b) TpCl-1, and (c) TpCl-2 of the present invention; Figure 3 The XPS spectra of TpPa, TpCl-1 and TpCl-2 of the present invention are (a) C 1s narrow spectrum; (b) N 1s narrow spectrum; (c) O1s narrow spectrum; (d) Cl 2p narrow spectrum; (e) full spectrum; Figure 4 The solid-state NMR carbon spectra of (a) TpPa, (b) TpCl-1, (c) TpCl-2 and the partial structural formulas of (d) TpPa, (e) TpCl-1, and (f) TpCl-2 of the present invention are shown; Figure 5 These are SEM images of (a, d) TpPa, (b, e) TpCl-1, and (c, f) TpCl-2 of the present invention; Figure 6 These are the nitrogen adsorption-desorption curves of (a) TpPa, (b) TpCl-1, and (c) TpCl-2 of the present invention (the insets in Figures ac are the pore size distribution test diagrams); Figure 7 The impedance test spectra of the solid electrolytes (a) TpPa, (b) TpCl-1, and (c) TpCl-2 of the present invention at temperatures of 298K to 358K; (d) is the Arrhenius diagram of the electrolytes TpPa, TpCl-1, and TpCl-2 (the insets of Figures ac are enlarged diagrams of the impedance high-frequency region); Figure 8 The migration number and electrochemical window tests of the electrolytes (a) TpPa, (b) TpCl-1, and (c) TpCl-2 of the present invention; (d) LSV tests of the electrolytes TpPa, TpCl-1, and TpCl-2 (the insets of Figures ac are impedance test diagrams before and after polarization, and the inset of Figure d is an enlarged diagram); Fig. 9 The stripping and plating behaviors of the electrolytes of the present invention (a) TpPa, (b) TpCl-1, and (c) TpCl-2 in symmetric lithium batteries (the inset is an enlarged view of different current densities); Fig.10 The constant current charge and discharge curves of the LFP|TpPa|Li battery of the present invention at different rates are (a) 1C; (b) 0.2C; (c) rate performance; (d) charge and discharge curve; Fig.11The constant current charge and discharge curves of the LFP|TpCl-1|Li battery of the present invention at different rates are (a) 1C; (b) 0.2C; (c) rate performance; (d) charge and discharge curve; Fig.12 The constant current charge and discharge curves of the LFP|TpCl-2|Li battery of the present invention at different rates are (a) 1C; (b) 0.2C; (c) rate performance; (d) charge and discharge curve; Fig.13 The constant current charge and discharge curve comparison diagrams at different rates of the present invention are (a) 1C; (b) 0.2C; (c) rate performance. DETAILED DESCRIPTION

[0014] In order to make the purpose and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0015] The instruments, reagents, materials, etc. involved in the following examples, unless otherwise specified, are all conventional instruments, reagents, materials, etc. in the prior art and can be obtained through regular commercial channels. The experimental methods, detection methods, etc. involved in the following examples, unless otherwise specified, are all conventional experimental methods, detection methods, etc. in the prior art.

[0016] Example 1 This embodiment provides a method for preparing a chlorine-containing COFs solid electrolyte. The chlorine-containing COFs solid electrolyte includes two types, specifically: TpCl-1 and TpCl-2; The preparation method of TpCl-1 is as follows: 210 mg of 2,4,6-triformylphloroglucinol (Tp) and 214 mg of 2-chloro-1,4-diaminobenzene (PaCl-1) are weighed and placed in 30 mL of a mixed solvent of mesitylene and 1,4-dioxane (volume ratio of 1:1), and 4 mL of 6 mol·L -1 of glacial acetic acid, and ultrasonicated until uniformly dispersed to obtain a mixed solution; under a nitrogen atmosphere, the mixed solution was sealed in a liquid nitrogen bath and repeatedly frozen-thawed three times, and after returning to room temperature, it was reacted at 120°C for 72 hours; after the reaction was completed, the obtained solid material was washed with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing liquid was colorless; finally, it was dried under reduced pressure at 90°C for 12 hours to remove the solvent to obtain a dark red powder, which is TpCl-1; The preparation method of TpCl-2 is as follows: 210 mg of 2,4,6-triformylphloroglucinol (Tp) and 265 mg of 2,5-dichloro-1,4-phenylenediamine (PaCl-2) are weighed and placed in 30 mL of a mixed solvent of mesitylene and 1,4-dioxane (volume ratio of 1:1), and 4 mL of 6 mol·L-1 of glacial acetic acid, and ultrasonicated until uniformly dispersed to obtain a mixed solution; under a nitrogen atmosphere, the mixed solution was sealed in a liquid nitrogen bath and repeatedly frozen and thawed three times, and after returning to room temperature, it was reacted at 120°C for 72 hours; after the reaction was completed, the obtained solid material was washed with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing liquid was colorless; finally, it was dried under reduced pressure at 90°C for 12 hours to remove the solvent to obtain a dark red powder, which is TpCl-2.

[0017] Comparative Example 1 Preparation of TpPa: 120 mg of 2,4,6-triformylphloroglucinol (Tp) and 108 mg of 1,4-phenylenediamine (Pa) were weighed and placed in 30 mL of a mixed solvent of mesitylene and 1,4-dioxane (volume ratio 1:1), followed by the addition of 4 mL of 6 mol·L -1 of glacial acetic acid, and ultrasonicated until uniformly dispersed; under a nitrogen atmosphere, the reaction mixture was sealed in a liquid nitrogen bath and repeatedly frozen and thawed three times. After returning to room temperature, it was reacted at 120°C for 72 hours; after the reaction was completed, the obtained solid material was washed with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing liquid was colorless; finally, it was dried under reduced pressure at 90°C for 12 hours to remove the solvent, and a red powder was obtained, which was the TpPa material.

[0018] Experimental Example 1 Structural Characterization 1. XRD analysis of TpPa, TpCl-1 and TpCl-2 Figure 1 Test XRD patterns for TpCl-1, TpCl-2, and TpPa and refine the patterns using MaterialsStudio. Figure 1 As shown in a, TpPa has diffraction peaks at 2θ=4.6° and 8.0°, corresponding to the (1, -1, 0) and (1, -2, 0) diffraction crystal planes of the material, respectively. Figure 1 As shown in bc, the diffraction peaks of TpCl-1 and TpCl-2 at 2θ=4.7° correspond to the (1, -1, 0) diffraction crystal plane of the material. Figure 1 As shown in Figure d, the error factors of the powder diffraction experimental value of TpPa material and the refined value after simulation are: Rwp=1.9%, Rp=1.5%; the error factors of TpCl-1 are: Rwp=2.2%, Rp=1.7%; the error factors of TpCl-2 are Rwp=2.5%, Rp=2.0%. The (1, -2, 0) diffraction crystal plane disappears due to chlorination, and the (1, -1, 0) diffraction crystal plane exists in all three COFs, indicating that the crystal form maintains the same arrangement and isovertical properties. The above tests show that TpPa, TpCl-1 and TpCl-2 were successfully synthesized.

[0019] 2. FT-IR analysis of TpPa, TpCl-1 and TpCl-2 Figure 2 The following are Fourier infrared spectra of TpPa, TpCl-1 and TpCl-2 raw materials and products. Figure 2 a, 2894cm -1 and 1640cm -1 They are the stretching vibrations of CH=O and C=O groups in the raw material 2,4,6-triformylphloroglucinol (Tp), 3373-3197 cm -1 The peak at 1572cm is the N–H stretching vibration in the raw material 1,4-phenylenediamine (Pa). This peak disappears in the product TpPa, indicating that the aldehyde group and the amino bond disappear. -1 and 1248cm -1 The stretching vibrations are C=C and C–N bonds, which are due to the condensation reaction between Tp and Pa. Figure 2 b, 3421-3333cm -1 The peak at 1581cm is the stretching vibration of N–H in the raw material 2-chloro-1,4-diaminobenzene (PaCl-1), which disappears in the product TpCl-1. -1 and 1267cm -1 They are the stretching vibrations of the C=C and C–N bonds in TpCl-1, which are caused by the condensation reaction between Tp and PaCl-1. Figure 2 c, 3423-3335cm -1 The peak at 1587cm is the stretching vibration of N–H in the raw material 2,5-dichloro-1,4-phenylenediamine (PaCl-2), which disappears in the product TpCl-2. -1 and 1254cm -1 The stretching vibrations of C=C and C–N bonds in TpCl-2 are due to the condensation reaction between Tp and PaCl-2. In the above infrared tests, the chemical bonds of the aldehyde and amino groups of TpPa, TpCl-1 and TpCl-2 disappeared, and new chemical bonds C=C and C–N were generated, indicating that TpPa, TpCl-1 and TpCl-2 were successfully synthesized.

[0020] 3. XPS analysis of TpPa, TpCl-1 and TpCl-2 Figure 3 Table 1 is the XPS spectra of TpPa, TpCl-1 and TpCl-2, and Table 2 is the relative content of each element in the full spectrum. Figure 3As shown in a, the carbon spectrum fitting peaks in TpPa are located at 284.4eV, 285.7eV, 287.0eV and 288.4eV, respectively, and are attributed to C=C, C–N, C=O and C–O–H; with the increase of chlorine content, the binding energy of C–N and C=O of TpCl-1 and TpCl-2 gradually decreases; the carbon spectrum fitting peak in TpCl-1 and TpCl-2 is located at 290.1eV and is attributed to C–Cl. Table 2 shows the distribution of the above carbon spectrum binding energy shift. Figure 3 As shown in b, the N1s narrow spectra of TpPa, TpCl-1 and TpCl-2 have two fitting peaks at 399.8eV and 403.3eV, respectively, for C–N and N–H bonds. Figure 3 As shown in Figure c, the oxygen spectrum fitting peaks in TpPa are located at 530.92eV and 533.03eV, respectively, and are attributed to C–O–H and C=O; the oxygen spectrum fitting peaks in TpCl-1 are located at 530.81eV and 532.35eV; the oxygen spectrum fitting peaks in TpCl-2 are located at 530.69eV and 532.28eV; Table 3 shows the above oxygen spectrum binding energy shift distribution. With the increase of chlorine content, the binding energy of C–O–H and C=O of TpCl-1 and TpCl-2 gradually decreases. Figure 3 d is the energy spectrum of Cl2p in TpCl-1 and TpCl-2 structures. The double peaks at 200.3eV and 201.9eV are Cl2p3 and Cl2p1, with an energy difference of 1.6eV, which is consistent with the full spectrum. Figure 3 e. In summary, TpPa, TpCl-1 and TpCl-2 all have C=C, C–N, C=O and C–O–H, indicating that TpPa, TpCl-1 and TpCl-2 were successfully synthesized.

[0021] Table 1 Relative contents of elements in TpPa, TpCl-1 and TpCl-2

[0022] Table 2 Comparison of XPS carbon spectra binding energy of TpPa, TpCl-1 and TpCl-2 (eV)

[0023] Table 3 Comparison of XPS oxygen spectrum binding energy of TpPa, TpCl-1 and TpCl-2 (eV)

[0024] 4. TpPa, TpCl-1, TpCl-2 13 CSSNMR analysis Figure 4 ac are the solid-state NMR carbon spectra tests of TpPa, TpCl-1 and TpCl-2, Figure 4 df are the chemical structures of TpPa, TpCl-1 and TpCl-2 respectively. Figure 4 As shown in a, the chemical shifts of 105.9 ppm and 183.6 ppm are attributed to the C=CN and C=O chemical bonds, and the chemical shift of 145.9 ppm is attributed to the CN chemical bond. Figure 4 As shown in Figure d, the characteristic peaks at chemical shifts of 116.4, 119.3 and 134.8 ppm are respectively attributed to the carbon bonds at positions e, d and c of the TpPa structural formula. Figure 4 As shown in b, the chemical shifts of 106.7 ppm and 183.3 ppm are attributed to the C=CN and C=O chemical bonds, and the chemical shift of 145.3 ppm is attributed to the CN chemical bond. Figure 4 As shown in e, the chemical shifts of the carbon bonds at positions h, g, e, d, and c in the TpCl-1 structure are 114.4, 118.9, 123.7, 131.6, and 134.6 ppm, respectively. Figure 4 As shown in c, the chemical shifts of 107.1ppm and 183.1ppm are attributed to the C=CN and C=O chemical bonds, and the chemical shift of 143.3ppm is attributed to the CN chemical bond. Figure 4 As shown in Figure f, the chemical shifts of the carbon bonds at positions g, d (e) and c in the TpCl-2 structure are 114.7, 122.7 and 131.8 ppm, respectively. The presence of the above C=CN, C=O and CN chemical bonds indicates that the materials TpPa, TpCl-1 and TpCl-2 were successfully synthesized and that there is an enol-keto interconversion in the structure. The asterisk (★) indicates the peak caused by the rotating sideband and the peak caused by the presence of small solvent molecules in the pores. The chemical bonds present in the solid-state NMR test are consistent with the test results of the infrared test and the energy spectrum, verifying that TpPa, TpCl-1 and TpCl-2 were successfully synthesized.

[0025] 5. SEM analysis of TpPa, TpCl-1 and TpCl-2 like Figure 5 As shown in the figure, the TpPa material is composed of aggregated particles, and the particles are tightly bound to each other. The microscopic morphology of the TpCl-1 material is uniform and fibrous. The TpCl-2 material has a clear shape and size distribution, presenting a regular nanorod structure with a rough surface.

[0026] 6. BET analysis of TpPa, TpCl-1, and TpCl-2 The N2 adsorption and desorption tests were carried out on TpPa, TpCl-1 and TpCl-2, with the pretreatment degassing temperature at 110°C and the degassing time at 24h. Figure 6 As shown, the specific surface areas of TpPa, TpCl-1 and TpCl-2 are 98m 2 g -1、334m 2 g -1 and 429m 2 g -1 ; The pore sizes are 3.8nm, 1.9nm and 3.8nm respectively. With the introduction of covalently bonded chlorine, its morphology changes significantly from granular to fibrous, so the specific surface area gradually increases. When only one chlorine atom replaces a hydrogen atom, its pore size decreases due to the increase in specific surface area. When two chlorine atoms replace hydrogen atoms, the symmetrical chlorine atoms play a role in expanding the pore size, increasing its pore size from 1.9nm to 3.8nm.

[0027] Experimental Example 2 Electrochemical Performance Test 1. Ionic conductivity test of TpPa, TpCl-1 and TpCl-2 In order to verify the electrochemical performance of COFs materials, the ionic conductivity of the electrolyte was studied by impedance testing. Figure 7 As shown in Figure ac, the AC impedance test spectra of electrolytes TpPa, TpCl-1 and TpCl-2 were tested in the temperature range of 25-85°C. The ionic conductivities of TpPa, TpCl-1 and TpCl-2 at room temperature are: 6.37×10 -4 Scm -1 , 3.02×10 -3 Scm -1 and 3.23×10 -3 Scm -1 When the temperature rises to 85℃, the ionic conductivity is: 2.00×10 -3 Scm -1 ,7.13×10 -3 Scm -1 and 7.77×10 -3 Scm -1 , the increase in temperature promotes the transmission of lithium ions. Within this temperature range, the ionic conductivity shows a linear relationship with the change in temperature, and its correlation coefficient r They are 0.99, 0.99 and 0.99 respectively, which conforms to the Arrhenius behavior. Figure 7 As shown in Figure d, the activation energies of electrolytes TpPa, TpCl-1 and TpCl-2 calculated by linear fitting of temperature and ionic conductivity are 0.18 eV, 0.14 eV and 0.14 eV respectively. Lower activation energy is conducive to faster movement of lithium ions between electrodes and electrolytes.

[0028] 2. Migration number and electrochemical window test of TpPa, TpCl-1 and TpCl-2 t + = Formula 1 t + —Lithium ion migration number; Io , Is —Initial current and steady-state current (mA); Ro , Rs —Initial impedance and impedance after polarization (Ω); ∆V—Polarization voltage (0.01 V).

[0029] The lithium ion migration numbers of TpPa, TpCl-1 and TpCl-2 electrolytes are calculated by formula 1 to be 0.75 ( Figure 8 a), 0.81 ( Figure 8 b) and 0.85 ( Figure 8 c) A higher migration number is conducive to the efficient transportation of lithium ions. Figure 8 As shown in Figure d, the stable cycle voltage ranges of TpPa, TpCl-1 and TpCl-2 electrolytes are 1.0-4V, 1.0-4.5V and 1.0-5.0V, respectively. Due to the presence of electron-withdrawing groups in the chlorinated 2-chloro-1,4-diaminobenzene and 2,5-dichloro-1,4-phenylenediamine structures, the COFs skeleton attracts more lithium ions while inhibiting the migration of anions, and the decomposition voltage of the electrolyte is also improved. All three COFs materials have high migration numbers and wide electrochemical windows, which are sufficient to match the LFP positive electrode material, indicating that their electrolytes TpPa, TpCl-1 and TpCl-2 can be used in solid-state lithium-ion batteries.

[0030] 3. Stripping electroplating test of TpPa, TpCl-1 and TpCl-2 The growth of dendrites and the change of interface volume during stripping and electroplating are important factors limiting the cycling of lithium metal batteries. The electrochemical performance of symmetrical lithium batteries, namely Li|TpPa|Li, Li|TpCl-1|Li and Li|TpCl-2|Li, was tested by steady-state charge and discharge. Fig. 9 As shown in a, the Li|TpPa|Li current density is 0.02 mA cm -2 , 0.05mAcm -2 , 0.1mAcm -2 and 0.2mAcm -2 When , the polarization voltages are 9mV, 28mV, 58mV and 200mV respectively. Fig. 9 As shown in b, the current density of Li|TpCl-1|Li is 0.02 mA cm -2 , 0.05mAcm -2 , 0.1mAcm -2 and 0.2mAcm -2When the polarization voltage is 9mV, 24mV, 50mV and 140mV respectively. Fig. 9 c shows that Li|TpCl-2|Li at a current density of 0.02 mA cm -2 , 0.05mAcm -2 , 0.1mAcm -2 and 0.2mAcm -2 When the current density increases, the polarization voltages are 8mV, 23mV, 60mV and 120mV respectively. The polarization voltages of symmetrical lithium batteries TpPa, TpCl-1 and TpCl-2 increase with the increase of current density. Under the same current density, the polarization voltages of TpCl-1 and TpCl-2 show a constant or decreasing pattern, indicating that the external voltage that can be tolerated remains unchanged or increases. This may be because the effect of –Cl and lithium slows down the growth of internal battery dendrites, and –Cl and Li + It has stable binding ability and has a certain inhibitory effect on the short circuit of the battery.

[0031] 4. Cyclic performance and rate performance test of TpPa, TpCl-1 and TpCl-2 like Fig.10 As shown in a, LFP|TpPa|Li is charged and discharged for 300 cycles at a current density of 1C, and the first cycle charge and discharge specific capacities are 101 mAh g -1 and 101mAhg -1 The final cycle charge and discharge capacity is 81 mAh g -1 and 81mAhg -1 , the discharge capacity retention rate is 80%. Fig.10 As shown in b, the LFP|TpPa|Li battery is charged and discharged for 300 cycles at a current density of 0.2C, and the first discharge and charge specific capacities are 147 mAh g -1 and 147mAhg -1 The final cycle charge and discharge capacity is 110 mAh g -1 and 111mAhg -1 , the discharge capacity retention rate is 76%. Fig.10 As shown in cd, the discharge specific capacities of LFP|TpPa|Li battery at different rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 0.2C and 0.1C are 159, 142, 131, 104, 76, 139 and 152 mAh g, respectively. -1 After 10 cycles at 2C, it can still recover to 152mAhg at 0.1C -1 The above results show that the application of TpPa in lithium-ion solid electrolytes is feasible.

[0032] like Fig.11As shown in a, the LFP|TpCl-1|Li battery is charged and discharged at a current density of 1C for 300 cycles, and the first cycle charge and discharge specific capacities are 128 mAh g -1 and 128mAhg -1 The final cycle charge and discharge capacity is 92 mAh g -1 and 91mAhg -1 , the discharge capacity retention rate is 71%. Fig.11 As shown in b, the LFP|TpCl-1|Li battery is charged and discharged at a current density of 0.2C for 300 cycles, and the first cycle charge and discharge specific capacities are 162 mAh g -1 and 161mAhg -1 The final cycle charge and discharge capacity is 132 mAh g -1 and 125mAhg -1 , the discharge capacity retention rate is 77%. Fig.11 As shown in cd, the LFP|TpCl-1|Li battery was cycled at different rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 0.2C and 0.1C, and its discharge specific capacity was 166, 160, 145, 127, 101, 150 and 154 mAh g, respectively. -1 After 10 cycles at 2C, it can still recover to 154mAhg at 0.1C. -1 The above results show that the application of TpCl-1 in lithium-ion solid electrolytes is feasible.

[0033] like Fig.12 As shown in a, the LFP|TpCl-2|Li battery is charged and discharged at a current density of 1C for 300 cycles, and the first cycle charge and discharge specific capacities are 131 mAh g -1 and 130mAhg -1 The final cycle charge and discharge capacity is 94 mAh g -1 and 93mAhg -1 , showing a discharge capacity retention rate of 71%. Fig.12 As shown in b, the LFP|TpCl-2|Li battery is charged and discharged for 300 cycles at a current density of 0.2C. The first cycle charge and discharge specific capacities are 165 mAh g -1 and 165mAhg -1 The final cycle charge and discharge capacity is 127 mAh g -1 and 125mAhg -1 , the discharge capacity retention rate is 75%. Fig.12As shown in cd, the LFP|TpCl-2|Li battery was cycled at different rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 0.2C and 0.1C, and its discharge specific capacity was 167, 162, 148, 129, 115, 154 and 157 mAh g, respectively. -1 After 10 cycles at 2C, it can still recover to 157mAhg at 0.1C -1 The above results show that the application of TpPa, TpCl-1 and TpCl-2 in lithium-ion solid electrolytes has certain research value.

[0034] like Fig.13 As shown in the figure, TpPa was used as the basic material for experimental research, and chlorinated 2-chloro-1,4-diaminobenzene and 2,5-dichloro-1,4-phenylenediamine were used as raw materials to prepare TpCl-1 and TpCl-2. The initial discharge experiment showed that the discharge specific capacities of TpPa, TpCl-1 and TpCl-2 batteries at 1C were 101, 128 and 130 mAh g, respectively. -1 ; The discharge capacity at 0.2C is increased to 147, 161 and 165 mAhg -1 , the corresponding rate performance remains consistent.

[0035] In this example, the TpPa, TpCl-1 and TpCl-2 materials were synthesized by a solvothermal method, and the successful synthesis of the materials was proved by characterizations such as XRD, FT-IR and XPS.

[0036] Compared with TpPa, the electrochemical performance of modified TpCl-1 and TpCl-2 is gradually enhanced. Thanks to the strong electron-withdrawing property of halogen chlorine, it can fix the free anions in the electrolyte system and make the movement speed of lithium ions in the electrolyte faster. The ionic conductivity of TpPa, TpCl-1 and TpCl-2 at room temperature is: 6.37×10 -4 Scm -1 , 3.02×10 -3 Scm -1 and 3.23×10 -3 Scm -1 The lithium ion migration numbers of the electrolytes TpPa, TpCl-1 and TpCl-2 are 0.75, 0.81 and 0.85 respectively, and the cycle stability voltage ranges are 1.0-4.0V, 1.0-4.5V and 1.0-5.0V respectively. For the current density range of 0.02-0.2mAcm -2, the operation of symmetrical cells shows that TpPa, TpCl-1 and TpCl-2 electrolytes and metal lithium electrodes have good interfacial stability. The LFP|TpCl-2|Li battery was charged and discharged for 300 cycles at a current density of 1C, with a discharge capacity retention rate of 71%. It was continuously charged and discharged for 300 cycles at a current density of 0.2C, with a discharge capacity retention rate of 75%. Rate performance tests show that TpPa, TpCl-1 and TpCl-2 full batteries can still recover a high specific capacity after high-rate cycling, indicating that the electrolyte has excellent reversibility. Due to the diversity of COFs material connection methods and raw material types, and the fact that both hydrazide and melamine are rich in amino structures and can undergo condensation reactions, different types of COFs compounds can be prepared.

[0037] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a chlorine-containing COFs solid electrolyte, characterized in that: The chlorine-containing COFs solid electrolyte includes two types, specifically: TpCl-1 and TpCl-2; The preparation method of TpCl-1 is as follows: weigh 2,4,6-triformylphloroglucinol and 2-chloro-1,4-diaminobenzene and place them in a mixed solvent of mesitylene and 1,4-dioxane, drop glacial acetic acid, and perform ultrasonication until uniform dispersion to obtain a mixed solution; under a nitrogen atmosphere, seal the mixed solution in a liquid nitrogen bath and freeze-thaw repeatedly three times, and react at 120° C. for 72 hours after returning to room temperature; after the reaction is completed, wash the obtained solid material with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing solution is colorless; finally, dry under reduced pressure at 90° C. for 12 hours to remove the solvent to obtain a dark red powder, namely TpCl-1; The preparation method of TpCl-2 is as follows: weigh 2,4,6-triformylphloroglucinol and 2,5-dichloro-1,4-phenylenediamine and place them in a mixed solvent of mesitylene and 1,4-dioxane, drop glacial acetic acid, and perform ultrasonication until uniform dispersion to obtain a mixed solution; under a nitrogen atmosphere, seal the mixed solution in a liquid nitrogen bath and repeatedly freeze-thaw it three times, and react at 120° C. for 72 hours after returning to room temperature; after the reaction is completed, wash the obtained solid material with acetone, methanol and tetrahydrofuran for 3-5 times respectively until the washing solution is colorless; finally, dry under reduced pressure at 90° C. for 12 hours to remove the solvent to obtain a dark red powder, namely TpCl-2.

2. The method for preparing a chlorine-containing COFs solid electrolyte according to claim 1, characterized in that: In the preparation of TpCl-1, the mass of 2,4,6-triformylphloroglucinol is 210 mg, and the mass of 2-chloro-1,4-diaminobenzene is 214 mg.

3. The method for preparing a chlorine-containing COFs solid electrolyte according to claim 1, characterized in that: In the preparation of TpCl-1, the volume of the mixed solvent is 30 mL; in the mixed solvent, the volume ratio of mesitylene to 1,4-dioxane is 1:1; the concentration of glacial acetic acid is 6 mol·L -1 , the volume is 4mL.

4. The method for preparing a chlorine-containing COFs solid electrolyte according to claim 1, characterized in that: In the preparation of TpCl-2, the mass of 2,4,6-triformylphloroglucinol is 210 mg, and the mass of 2,5-dichloro-1,4-phenylenediamine is 265 mg.

5. The method for preparing a chlorine-containing COFs solid electrolyte according to claim 1, characterized in that: In the preparation of TpCl-2, the volume of the mixed solvent is 30 mL; in the mixed solvent, the volume ratio of mesitylene to 1,4-dioxane is 1:1; the concentration of glacial acetic acid is 6 mol·L -1 , the volume is 4mL.

6. A chlorine-containing COFs solid electrolyte prepared by the method for preparing a chlorine-containing COFs solid electrolyte according to any one of claims 1 to 5.

7. Use of the chlorine-containing COFs solid electrolyte as claimed in claim 6 in the preparation of lithium metal batteries.

Citation Information

Patent Citations

  • Lithium-rich PAF composite single-ion quasi-solid polymer electrolyte, preparation method and application

    CN116706225A

  • Donor-receptor linked covalent organic framework-based solid electrolyte as well as preparation method and application thereof

    CN118290681A

  • COFs material and preparation method thereof, lithium battery positive electrode material and application thereof

    CN118440273A

Cited By

  • Modified gel electrolyte, preparation method thereof and lithium battery

    CN122338203A